Bottlebrush Polymer Synthesis by Ring-Opening Metathesis Polymerization: The Significance of the Anchor Group - Radzinski, Scott C; Foster, Jeffrey C; Chapleski, Robert C; Troya, Diego; Matson, John B (Journal of the American Chemical Society, 2016)
Control over bottlebrush polymer synthesis by ring-opening metathesis polymerization (ROMP) of macromonomers (MMs) is highly dependent on the competition between the kinetics of the polymerization and the lifetime of the catalyst. We evaluated the effect of anchor group chemistrythe configuration of atoms linking the polymer to a polymerizable norborneneon the kinetics of ROMP of polystyrene and poly(lactic acid) MMs initiated by (H2IMes)(pyr)2(Cl)2RuCHPh (Grubbs third generation catalyst). We observed a variance in the rate of propagation of >4-fold between similar MMs with different anchor groups. This phenomenon was conserved across all MMs tested, regardless of solvent, molecular weight (MW), or repeat unit identity. The observed >4-fold difference in propagation rate had a dramatic effect on the maximum obtainable backbone degree of polymerization, with slower propagating MMs reducing the maximum bottlebrush MW by an order of magnitude (from ∼106 to ∼105 Da). A chelation mechanism was initially proposed to explain the observed anchor group effect, but experimental and computational studies indicated that the rate differences likely resulted from a combination of varying steric demands and electronic structure among the different anchor groups. The addition of trifluoroacetic acid to the ROMP reaction substantially increased the propagation rate for all anchor groups tested, likely due to scavenging of the pyridine ligands. Based on these data, rational selection of the anchor group is critical to achieve high MM conversion and to prepare pure, high MW bottlebrush polymers by ROMP grafting-through.